Pemberdayaan Orang Tua Dan Guru Untuk Peningkatan Perlindungan Anak Di Desa Sungai Pinang Kecamatan Hulu Kuantan Kabupaten Kuantan Singingi - Risma, Devi; Satria, Defni; Solfiah, Yeni; N, Zulkifli; Mastuinda, Mastuinda; Pratiwi, Nanda (Journal Of Human And Education (JAHE), 2024)
The goal of the Community Service activity is to enhance the understanding and capacity of parents and teachers in protecting early childhood through comprehensive training activities. This program targets several significant outcomes, including increased knowledge and skills among parents and teachers, particularly regarding child protection issues. The community service activity titled “Empowering Parents and Teachers to Improve Child Protection in Sungai Pinang Village, Hulu Kuantan Subdistrict, Kuantan Singingi Regency” involved parents and teachers. The activity began with a focus group discussion (FGD) as initial preparation before the workshop was conducted. It was followed by a face-to-face workshop with the subjects of the community service. A classical approach was used to deliver material related to improving child protection in Sungai Pinang Village, Hulu Kuantan Subdistrict, Kuantan Singingi Regency. Through this educational activity on child protection for parents and teachers, it is hoped that they will gain a comprehensive understanding of child protection. Consequently, parents will be able to reduce violent behaviors towards children, especially those considered normal in child education. Thus, the rate of child violence is expected to decrease, leading to the development of high-quality children as the future generation of the nation.